Track student attendance at a time of the covid-19 pandemic using location-finding technology - Julaily Aida, Jusoh; Ahmad Nazari, Mohd Rose; Syarilla Iryani, A. Saany; Yousef A. Baker, El-Ebiary (2021)
With the improvement of innovation that has become increasingly unexpected and modern, the use of cell phones has become the primary option in supervising various issues of life. The Covid - 19 episode is starting to take the course to move from learning strategies to open distance learning. Open distance learning is an idea where students rate addresses from different locations. Among the exercises affected by this change is the way to record student participation and collaboration through web addresses, rather than the usual way of being in a similar classroom while talking. Global Positioning System (GPS) is a global satellite path frame that provides area and time synchronization. This methodology can help teachers monitor their students' attitudes throughout the learning meeting. GPS activity is based on the triangulation technique where the area is determined by estimating the distance to the satellites. Accordingly, iHadir was recommended to overcome the issue of pursuing student participation. iHadir is a versatile application framework that can find the student 's area during a learning meeting. This app can be used as another option in checking student engagement during web-based learning. IHadir will help increase the validity of sharing records during web-based learning.